Circle CPP
Circle CPP
Circle CPP
y at the origin and passes through (3, 4) is- x2 + y2 + 4x – 4y + 4 = 0 which make equal
45 intercepts on the positive coordinate axes, is
(A) 2(x2 + y2) – x = 0 (B) 3(x2 + y2) – 25x = 0
3 (A) x + y = 2 (B) x + y = 2 2
(C) 4(x2 + y2) – 25x = 0 (D) None of these (C) x + y = 4 (D) x + y = 8
2 The equation of a circle passing through (3, –6) and 8 Length of intercept made by line x + y = 2 on the
touching both the axes is -
circle x2 + y2 – 4x – 6y – 3 = 0 is -
(A) x2 + y2 – 6x + 6y + 8 = 0
(A) 2 23 (B) 23 (C) 46
(B) x2 + y2 + 6x – 6y + 9 = 0
(C) x2 + y2 + 30x – 30y + 225 = 0 (D) 4 23
(D) x2 + y2 – 30x + 30y + 225 = 0 9 If the line 3x + 4y = m touches the circle
3 The abscissae of two points A and B are the roots of x2 + y2 = 10x, then m is equal to -
the equation x2 + 2ax – b2 = 0, and their ordinates (A) – 40, 10 (B) 40, – 10
are the roots of the equation (C) 40, 10 (D) –40, –10
x2 + 2px – q2 = 0. The radius of the circle with AB 10 The value of p so that the straight line
as diameter is x cos + y sin – p = 0 may touch the circle
(A) 2 2
a b p q 2 2
(B) a 2
p 2 x2 + y2 – 2ax cos – 2by sin – a2 sin2 = 0 is -
(C) b2 q2 (D) None of these (A) acos2 + bsin2 – a 2 b 2 sin 2
4 The parametric equations of the circle (B) acos2 – bsin2 – a 2 b 2 sin 2
x2 + (y + )2 = a2 is - (C) acos2 + bsin2 – a 2 – b 2 sin 2
(A) x = a cos, y = a sin +
(D) None of these
(B) x = a cos, y = a sin – 11 The equation of the normal of the circle
(C) x = a sin, y = a cos – (D) None of these 2x2 + 2y2 – 2x – 5y – 7 = 0 passing through the
5 The equation to the circle which passes through the point (1, 1) is
points (1, – 2) and (4, –3) and which has its centre on (A) x + 2y – 3 = 0 (B) 2x + y – 3 = 0
the straight line 3x + 4y = 7 is – (C) 2x + 3y – 5 = 0 (D) None of these
(A) 15x2 + 15y2 + 94x + 18 y + 55 = 0 12 If 3x + y = 0 is a tangent to the circle with centre at the
(B) 15x2 + 15y2 – 94x – 18 y + 55 = 0 point (2, –1), then the equation of the other tangent to
(C) 15x2 + 15y2 – 94x + 18 y + 55 = 0 the circle from the origin is -
(D) 15x2 + 15y2 + 94x – 18 y – 55 = 0 (A) x – 3y = 0 (B) x + 3y = 0
6 If x2 + y2 – 6x + 8y – 11 = 0 is a given circle and (0, (C) 3x – y = 0 (D) 2x + y = 0
0), (1, 8) are two points, then - 13 From a point P(16, 7), tangent PQ and PR are drawn
(A) Both the points are inside the circle to the circle x2 + y2 – 2x – 4y – 20 = 0. If C be the
(B) Both the points are outside the circle centre then area of the quadrilateral PQCR will be-
(C) One point is on the circle another is outside the (A) 75 (B) 150 (C) 15 (D) None
circle 14 If OA and OB be the tangents to the circle
(D) One point is inside and another is outside the x2 + y2 – 6x – 8y + 21 = 0 drawn from the origin O,
circle. then AB =
4 17
(A) 11 (B) 21 (C) (D) None
5 3
24 The equation of the diameter of the circle
2
15 The equation of the chord of contact of the circle x x2 + y2 – 2x + 4y = 0 passing through the origin is-
+ y2 + 4x + 6y – 12 = 0 with respect to the point (2, (A) x + 2y = 0 (B) x – 2y = 0
–3) is - (C) 2x + y = 0 (D) 2x – y = 0
(A) 4x = 17 (B) 4y = 17 25 Circles x + y = 4 and x + y2 – 2x – 4y + 3 = 0
2 2 2
Q.15 The Locus of the middle point of chords of Q.22 The members of a family of circles are given
the circle x2 + y2 = a2 which passes through by the equation 2(x2 + y2) + x – (1 + 2) y –
the fixed point (h, k) is . 10 = 0. The number of circles belonging to
(A) x2 + y2 – hx – ky = 0 the family that are cut orthogonally by the
(B) x2 + y2 + hx + ky = 0 fixed circle
(C) x2 + y2 – 2hx – 2ky = 0 x2 + y2 + 4x + 6y + 3 = 0 is
(D) None of these (A) 2 (B) 1
Q.16 If the circle x2 + y2 + 4x + 22y + c = 0 bisects (C) 0 (D) None of these
the circumference of the circle
x2 + y2 – 2x + 8y – d = 0, then c + d = Q.23 The circle passing through three distinct
(A) 60 (B) 50 (C) 40 (D) 56 points
Q.17 The equation of a circle is x 2 + y2 = 4. The (1, t), (t, 1) and (t, t) passes through the point
centre of the smallest circle touching this (A) (1, 1) (B) (–1, –1)
circle and the line x + y = 52 has the (C) (–1, 1) (D) (1, –1)
coordinates
Q.24 If the radical axis of the circles
7 7 3 3
(A) , (B) , x2 + y2 + 2gx + 2fy + c = 0 and
2 2 2 2 2 2
2x2 + 2y2 + 3x + 8y + 2c = 0 touches the
7 7 circle
(C) – ,– (D) None
2 2 2 2 x2 + y2 + 2x + 2y + 1 = 0, then
of these (A) g = 3/4 and f 2 (B) g 3/4 and f = 2
Q.18 The circle x2 + y2 – 2px = a2 – p2 lies within (C) g = 3/4 or f = 2 (D) None of these
the circle x2 + y2 – 2qx = b2 – q2 if
(A) p2 + q2 – a2 – b2 < 2 (pq – ab) Q.25 The coordinates of the radical centre of the
(B) p2 + q2 – a2 – b2 > 2 (pq – ab) three circles x2 + y2 = 9, x2 + y2 – 2x – 2y = 5
(C) p2 + q2 – a2 – b2 < 2 (pq + ab) and x2 + y2 + 4x + 6y = 19 are
(D) None of these (A) (– 1, 1) (B) (1, – 1)
Q.19 For the circle x2 + y2 – 2x – 6y + 1 = 0 the (C) (1, 1) (D) (0, 0)
chord of minimum length and passing
Q.26 The radical centre of three circles described
through (1, 2) is of length-
on the three sides of a triangle as diameter is
(A) 2 2 (B) 4 2 (C) 6 2 (D) 8 2
the
Q.20 The equation of a chord of the circle
(A) orthocentre (B) circumcentre
x2 + y2 + 4x – 6y = 0 is given by x + 2y = 0.
(C) incentre (D) centroid
The equation of the circle described on this
chord as diameter is
(A) 5(x2 + y2) + 28x + 14y = 0
(B) 5(x2 + y2) + 28x – 14y = 0
ab
(C)
One or more than one correct answer a b a 2 b2
ab
(D)
a b a 2 b2
Q.27 P(2, 2) is a point on the circle x 2 + y2 = 4
Q.32 The equation of one of the tangents from
and Q is another point on the circle such that
(1, 1) to a circle with its centre at (3, 0) is
arc
3x + y – 4 = 0. The equation of the other tangent
1 is-
PQ = × circumference. The coordinates
4 (A) 5x – y – 4 = 0 (B) 3y – x – 2 = 0
of Q are (C) 3y + x – 4 = 0 (D) 3x – y – 2 = 0
(A) (–2, –2) (B) (2, –2)
Q.33 Equation of circles which pass through the
(C) (–2, 2) (D) None of these
point (1, –2) and (3, –4) and touch the x-axis
Q.28 If A and B are two points on the circle is-
x2 + y2 – 4x + 6y – 3 = 0 which are farthest (A) x2 + y2 + 6x + 2y + 9 = 0
and nearest respectively from the point (7, 2) (B) x2 + y2 + 10x + 20y + 25 = 0
then (C) x2 + y2 – 6x + 4y + 9 = 0
(A) A = (2 – 22, – 3 – 22) (D) None of these
(B) B = (2 + 22, – 3 + 22)
(C) A = (2 + 22, – 3 + 22)
(D) B = (2 – 22, – 3 + 22)